Real currency appreciation in accession countries: Balassa-Samuelson and investment demand - Christoph Fischer (Bank of Finland, Institute for Economies in Transition (BOFIT), 2002)
The Balassa-Samuelson effect is usually seen as the prime explanation of the continuous real appreciation of central and east European (CEE) transition countries' currencies against their western counterparts.The response of a small country's real exchange rate to various shocks is derived in a simple model.It is shown that productivity shocks work not only through a Balassa-type supply channel but also through an investment demand channel. Therefore, empirical evidence apparently in favour of Balassa-Samuelson effects may require a re-interpretation.The model is estimated for a panel of CEE countries.The results are consistent with the model, plausibly explain the observed real appreciation and support the existence of the proposed investment demand channel.
URN:NBN:fi:bof-201408072161
Keywords: F31; F41; C33; 330